Pengaruh Pengawasan Langsung dan Tidak Langsung Terhadap Kinerja Pegawai Di Kantor Kementerian Agama Kabupaten Tasikmalaya - Astri Siti Fatimah (Jurnal Studi Sosial dan Politik, 2017)
This research aims to obtain data and information relating to the supervision and performance of employees. Research methods used in this research is descriptive research method of analysis. Then the data obtained processed and compiled up to gained clarity about the influence of the variable variable bound against free. Data collection techniques used through three ways: 1) observation (direct observation against the object of the research); 2) interviews; 3 question form); 4) study of the documentation. Based on a number of data research results and hypothesis test results by using path analysis (path analysis), it can be concluded that the direct and indirect supervision has a significant influence on performance of religious Ministry Office clerk in Tasikmalaya Regency. The magnitude of the influence on performance of such oversight specified direct and indirect supervision. The greatest contribution given by direct supervision then followed by indirect supervision.